Accroissement du sens de l’identité personnelle et sociale au cours de la transition études/travail - Fournier, Geneviève; Bujold, Charles (Canadian Journal of Counselling and Psychotherapy, 2007)
The goal of this article is to examine whether having a job, the full-time or part-time status of this job, and its nature, are predictors of growth in personal and social identity during the school-to-work transition. The results of two studies indicate that (1) having a job and (2) having a job that is congruent with one's training are predictors of growth in both personal and social identity, and that (3) having a full-time job is a predictor of growth in only personal identity.